Improving Approaches to Determining the Maximum Area of Land Parcels Under Existing Buildings and Structures - Martyn А.; Hunko, L.; Chumachenko, O.; Synieutskyi А. (Land Management, Cadastre and Land Monitoring, 2025)
The article substantiates directions for improving the methodological framework for forming state- and municipal-owned land parcels on which buildings and structures are located. A methodology is proposed for delineating such state and municipal land parcels that, in the course of parcel formation, explicitly accounts for the functional (land-use) designation, the technical specifications of buildings and structures, and their location in relation to other immovable property, red lines (street right-of-way lines), public-use areas and facilities, water bodies, territories and assets of the nature reserve fund, cultural heritage sites, and other objects that impose special land-use regimes. It is proposed to establish a unified, quantitatively measurable approach to determining the permissible boundaries of these parcels through two interrelated parameters—the width of a basic service strip and a special adjustment coefficient for each class of buildings and structures. The proposed approach to forming state- and municipal-owned land parcels hosting buildings and structures will, overall, simplify the work of compilers of land management documentation by relying on a single set of quantitative parameters. At the same time, it will reduce instances of transferring excessive land areas without competitive bidding and accordingly increase the supply of land on the competitive market. Keywords: land parcel formation, functional (land-use) designation, building codes.